Imaging findings of primary breast sarcoma: Results of a first multicenter study. Issue 88 (March 2017) - Wienbeck, Susanne; Meyer, Hans Jonas; Herzog, Aimee; Nemat, Sogand; Teifke, Andrea; Heindel, Walter; Schäfer, Fritz; Kinner, Sonja; Müller-Schimpfle, Markus; Surov, Alexey
Abstract: Purpose: To investigate imaging findings in patients with primary breast sarcoma (PBS). Materials and methods: A retrospective search in the databases of 10 radiological departments in Germany from 2000 to 2011 was performed. Only histologically proven cases of PBS were included into the study. Mammography was available in 31 patients (33 lesions), ultrasound images in 24 patients (24 lesions), and for 10 patients (14 lesions) magnetic resonance imaging (MRI) of the breast was performed. The breast findings were classified according to the American College of Radiology Breast Imaging Reporting and Data Systems (BI-RADS) 5th edition categories. Collected data were evaluated by means of descriptive statistics. Results: Forty-two female patients (mean age 62.0 years, range, 30–86 years) were included in the study. Clinically, all women had painless lumps. Irregular (53.3% [16/30]) or oval (30.0% [9/30]) mass with indistinct (73.3% [22/30]) or microlobulated (10% [3/30]) margins were common findings on mammograms. Ultrasound revealed typically an irregular (79.2% [19/24]), hypoechoic (62.5% [15/24]) mass, with indistinct margins (79.2% [19/24]), and posterior acoustic shadowing (79.2% [19/24]). MRI showed irregular masses (81.8% [9/11]) with irregular or spiculated margins, and a rapid initial signal increase with a delayed washout in kinetic analysis. Conclusion: Overall, PBS has no pathognomonic imaging features and can mimic those of invasive mammary carcinoma. Breast sarcoma should be taken into the differential diagnosis of breast findings described above.